2012
DOI: 10.1111/vde.12001
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships in three species of canine Demodex mite based on partial sequences of mitochondrial 16S rDNA

Abstract: Demodex canis and D. injai are two different species, with a genetic distance of 23.3%. It would seem that the short-bodied Demodex mite D. cornei is a morphological variant of D. canis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 33 publications
(39 reference statements)
2
38
0
2
Order By: Relevance
“…Short bodied mites of the genus Demodex have been reported in humans 15) , Syrian hamsters 10) , dogs 3,11) , cats 5) , ferrets 9) , and the Mediterranean water shrew 1) . Recently it has been suggested on the basis of mitochondrial rDNA analyses that short-tailed forms in dogs and humans may be morphological variants of longer tailed Demodex species as opposed to separate species 3,11,15) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Short bodied mites of the genus Demodex have been reported in humans 15) , Syrian hamsters 10) , dogs 3,11) , cats 5) , ferrets 9) , and the Mediterranean water shrew 1) . Recently it has been suggested on the basis of mitochondrial rDNA analyses that short-tailed forms in dogs and humans may be morphological variants of longer tailed Demodex species as opposed to separate species 3,11,15) .…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been suggested on the basis of mitochondrial rDNA analyses that short-tailed forms in dogs and humans may be morphological variants of longer tailed Demodex species as opposed to separate species 3,11,15) . However, there appears to be disagreement as to the conclusions reached by different authors using this methodology in the dog 3,11) . In contrast, a similar study in the cat concluded that the short-tailed mite, Demodex gatoi, is a distinct species from the longer tailed form, Demodex cati 5) .…”
Section: Discussionmentioning
confidence: 99%
“…We amplified a 338-bp DNA fragment of the mitochondrial 16S rRNA gene. We used the PCR conditions described in Sastre et al [18]. Briefly, PCR mixture was prepared in a 20μl reaction containing 5 μl of diluted DNA, PCR buffer (x1), 1.5 mmol⁄L MgCl2, 0.2 mmol⁄L of each dNTP, 0.5 μmol/L of each primer and 1 U AmpliTaq Gold DNA Polymerase (Life Technologies Corp.).…”
Section: Methodsmentioning
confidence: 99%
“…The taxonomic relationships of Demodex mites have also been estimated using the nuclear 18S rRNA gene [19,22]. While the 16S rRNA gene provides more discrimination at lower taxonomic levels [14,18,20,32,33], the 18S rRNA gene is considered more appropriate for classifications at the level of phyla and superphyla [34,35]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation